Recent developments in South African company law in respect of offers of compromise and schemes of arrangement between a company and its creditors and/or members in terms of section 311 of the Companies Act no. 61 of 1973, as amended - Getz, Keith (Department of Commercial Law, 2024)
A company may wish to negotiate, or indeed be forced to negotiate, with its members and/or creditors with a view to modifying rights or claims in their common interest. Such rights or claims against a company often vest in a large number of members or creditors with whom it would be impossible for a company to negotiate individually. Section 311 of the Companies Act No. 61 of 1973, as amended ("the Act"), in providing for a compromise or arrangement between a company and its members and/or creditors (or a class of them), provides a statutory procedure, subject to supervision by the courts, whereby a company can negotiate with its members and/or creditors (or a class of them) collectively and bind such members or creditors to proposals agreed upon by a majority of such members or creditors. Section 311 makes provision for the reaching of binding ,agreement between a company and its members and/or creditors in a manner which modifies rights upon a majority vote subject to certain safeguards of the rights of dissenting minorities.